Professional chaplaincy
1 online resource (100 pages)
Keywords: Choose innovative strategies for ministering to patients, families, and staff in a time of change! In the scramble to cut health care costs and the need to make every penny count, the hospital chaplaincy program is at serious risk for being trimmed or eliminated. Professional Chaplaincy: What Is Happening to It During Health Care Reform? offers a clear look at the current situation and positive suggestions for showing administrators just how essential chaplaincy is.This essential volume includes original research showing the specific consequences of the new emphasis on economic rationalism, as well as moving firsthand accounts of the effects of downsizing and budget cuts. An Australian case study catalogs and analyzes the outcomes of a drive for cost efficiency in a hospital chaplain department. A thorough literature review provides opportunities for chaplains and administrators to investigate the value of pastoral care in hospital settings.Professional Chaplaincy includes practical suggestions for ways to respond to budget cuts, such as: redefining the scope of your ministry strengthening community ties ministering to staff worried about heath care reform efforts offering new programs to enrich spiritual life documenting pastoral care visits researching the value of chaplaincy to the well-being of patients and familiesProfessional Chaplaincy offers positive ways that hospital chaplains can take action in response to the new health care paradigm. This informative book will assist you in developing future plans for maintaining and improving your hospital ministry.